Problems and Risks of Digitalization in Higher Education - M. V. Pashkov; V. M. Pashkova (Высшее образование в России)
The article offers a critical analysis of the impact of digital technologies on higher education. The authors discuss digitalization of higher education in relation to broader sociocultural and political and economic challenges: globalization, commercialization, socio-economic inequality, and ethical issues of technology application. Using this approach, the authors demonstrate that first of all, the rapid digitalization of higher education during the pandemic has activated some of the existing tension points and problematic trends: ‘McDonaldization’ of education, managerialism in higher education governance, the consumerist attitude to learning, the development of the elite education model, etc. Secondly, digitalization has introduced new risks related to the growing influence of global technology companies, online modes of the commodification of learning, the digital divide as a factor of educational inequality, and new ethical challenges. If these risks are not timely addressed, it may jeopardize the creative self-organization of educators and students, hinder the development of diverse and ethically responsible practices of technology use, and further make the higher education system unbalanced and more dependent on commercial technology companies. To mitigate the risks, the authors recommend that the academic community scrutinize the educational principles and ideas that are currently guiding the development of educational digital technologies. Furthermore, the academic community should take a proactive stance on how these technologies should work, and which pedagogical and ethical principles should inform their design. It is likewise essential to support the development of alternative models of digital technologies for education to be designed in partnership with all stakeholders in higher education.